Increasing Population of Daphnia Magna Natural Feed Using the Probiotic Effective Microorganisms-4 (EM4) - Muklisnah Djalil; Yuniarti Koniyo; Mulis Mulis (The NIKe Journal, 2020)
This study aims to determine the effectiveness dose of EM4 (Effective Microorganism-4) pro-biotic to increase the population of Daphnia magna natural feed. This study used a completely randomized design (CRD) with three treatments and three replications. The treatment in this study used pro-biotic EM4 with a dose of 1 ml for treatment A, a dose of 3 ml for treatment B. 5 ml dose for treatment C and a dose of 7 ml for treatment D. The highest population growth rate was found in treatment A dose 1 ml. Followed by treatment B with a dose of 3 ml, treatment C at a dose of 5 ml and the lowest at treatment D at a dose of 7 ml with values of 0.29, 0.09, 0.05 and 0.03 respectively. ANOVA analysis showed that the provision of pro-biotic EM4 had an effect on the population growth rate of Daphnia magna. The data from the further test of the least significant difference (LSD) showed that treatment A was significantly different from treatment B, C and D. Treatment B, C and D were not significantly different. The results of water quality measurements for temperatures ranging from 26-29 ° C, pH ranges from 5-6 and Dissolved Oxygen (DO) ranges from 4.4-4.9 mg / liter. This condition is the optimum range in Daphnia magna culture. Keywords: Daphnia magna; EM4 (Effective Microorganisme-4); population increase